Bioavailability of gallic acid and catechins from grape seed polyphenol extract is improved by repeated dosing in rats: Implications for treatment in Alzheimer’s Disease - Ferruzzi, Mario G. (2009)
The present study explored the bioavailability and brain deposition of a Grape Seed Polyphenolic Extract (GSPE) previously found to attenuate cognitive deterioration in a mouse model of Alzheimer’s disease (AD). Plasma pharmacokinetic response of major GSPE phenolic components was measured following intragastric gavage of 50, 100 and 150 mg GSPE per kg BW. LC-MS analysis identified gallic acid (GA), catechin (C), epicatechin (EC) in plasma of rats gavaged acutely with GSPE. Additionally, 4-methylgallic acid (4-OMeGA), 3′-methytlcatechin (3′-OMeC) and 3′-methylepicatechin (3′-OMeEC) were identified as circulating metabolites of GSPE phenolic constituents. C(max) for individual GSPE constituents and their metabolites increased in a dose-dependent fashion (with increasing GSPE oral dose). Repeated daily exposure to GSPE was found to significantly increase bioavailability (defined as plasma AUC(0-8h)) of GA, C and EC by 198, 253 and 282% relative to animals receiving only a single acute GSPE dose. EC and C were not detectable in brain tissues of rats receiving a single GSPE dose but reached levels of 290.7±45.9 and 576.7±227.7 pg/g in brain tissues from rats administered GSPE for 10 days. This study suggests that brain deposition of GA, C and EC is affected by repeated dosing of GSPE.